2000
DOI: 10.1002/1099-0879(200010)7:4<296::aid-cpp262>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Insecure attachment as a risk factor for psychopathology: the role of stressful events

Abstract: Attachment theory predicts that attachment styles 'learned' in previous relational experiences affect the way people cope with stressful events and, consequently, their mental health. The present study tested two mediational models of the relationships between stressful events, attachment style and psychopathology in a sample of 51 student couples. No evidence was found for a mediating role of attachment style in the relationship between stressful events and psychopathology, i.e. attachment style did not influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…Attachment theorists claim that early family experiences that are dysfunctional, through insensitive or non-responsive parenting lead to the development of insecure attachment (e.g., Booth, Rose-Krasnor, McKinnon & Rubin, 1994;Bowlby, 1977;Pieglage, Gerlsma, & Schaap, 2000). Related to this, it is argued that insecurely attached children are unable to draw on appropriate cognitive/affective coping strategies (Carlson & Sroufe, 1995;Svanberg, 1998).…”
supporting
confidence: 64%
“…Attachment theorists claim that early family experiences that are dysfunctional, through insensitive or non-responsive parenting lead to the development of insecure attachment (e.g., Booth, Rose-Krasnor, McKinnon & Rubin, 1994;Bowlby, 1977;Pieglage, Gerlsma, & Schaap, 2000). Related to this, it is argued that insecurely attached children are unable to draw on appropriate cognitive/affective coping strategies (Carlson & Sroufe, 1995;Svanberg, 1998).…”
supporting
confidence: 64%
“…When the related literature is investigated, is it seen that the studies of Pielage, Gerlsma and Schaap (2000) are of supportive nature of the results of this study. Pielage, Gerlsma and Schaap (2000) have investigated whether insecure attachment is a mediator variable between stress and psychopathology (carrier) or whether it is a causal variable leading to psychopathology by increasing stress (independent).…”
Section: Discussionmentioning
confidence: 99%
“…Pielage, Gerlsma and Schaap (2000) have investigated whether insecure attachment is a mediator variable between stress and psychopathology (carrier) or whether it is a causal variable leading to psychopathology by increasing stress (independent). These researchers have found that insecure attachment pattern is more of a causal factor than a mediator variable; and that in fact stressful incidents mediate on the link between attachment styles and psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because secure attachment is a protective factor (e.g., Prior & Glaser, 2006; Schore, 2001; Sroufe 2005), it was hypothesized that those who present this kind of attachment report also higher scores of positive transgender identity, whereas those who present insecure attachment styles are higher in internalized transphobia. Consequently, as the insecure attachment could represent a factor of vulnerability (Abdul Kadir & Bifulco, 2013; Pielage et al, 2000), a final hypothesis was that transgender people with insecure attachment styles are more likely to present higher levels of internalized transphobia.…”
mentioning
confidence: 99%